Hydrogenation of unactivated enamines to tertiary amines: rhodium complexes of fluorinated phosphines give marked improvements in catalytic activity - Tin, Sergey; Fanjul, Tamara; Clarke, Matthew L. (Beilstein Journal of Organic Chemistry, 2015)
In the hydrogenation of sluggish unactivated enamine substrates, Rh complexes of electron-deficient phosphines are demonstrated to be far more reactive catalysts than those derived from triphenylphosphine. These operate at low catalyst loadings (down to 0.01 mol %) and are able to reduce tetrasubstituted enamines. The use of the sustainable and environmentally benign solvent (R)-limonene for the reaction is also reported with the amine isolated by acid extraction.
Keywords: alkenes; homogeneous catalysis; hydrogenation; renewable solvents; tertiary amines